Kristologien i Grundtvigs salmer - Nielsen, Jakob Fløe (Grundtvig-studier, 1989)
The Christology in the Hymns of Grundtvig By Jakob Fløe Nielsen. The intention of the paper is to show the coherent and complete Christological conception that lies behind the many specific christological expressions in Grundtvig’s hymns, a christology that was never thoroughly elaborated by Grundtvig himself. The superior christological scheme is the descent and abasement of the Son of God from heaven to the land of death and the following exaltation to divine glory. Grundtvig’s strong emphasis upon man’s preserved image of God in spite of the Fall has, however, the consequence that the exaltation mentioned becomes a threefold presentation: 1. the resurrection and ascension of Christ in person repeating itself in history, 2. Christ passing through the seven leading churches of Christianity in his Word (especially in the words of the sacraments) towards the final transfiguration of the world, and 3. at the same time Christ fulfilling his own exaltation in the form of "the hope of glory" (Colossians 1.27) within each baptized. The background to this third aspect is Grundtvig’s concept of the fact that Christ offers himself to the faith in the words at baptism and Eucharist. In spite of the fall he here melts together with the preserved image of God within the believer. So at the same time as the fallen human being is reborn through baptism as the child of God, Christ is born as the tender hope of glory in the believer in the meeting of the word of the Holy Spirit and the human faith. The growth of Christ within the believing baptized is identical with that person’s transfiguration, as man’s destination from creation is realized: to be in the image of his God.In this process the Eucharist plays a decisive part. Where the words of institution are heard and believed, it signifies Christ’s victory over Satan within the baptized, and is also an expression of Christ inspiring his heavenly love into man to strengthen and glorify his earthly and powerless love. Thus, the christology in Grundtvig’s hymns in addition to being a description of a past event also becomes the rendering of the ongoing struggle between God and Satan in history and within the life of each Christian.